Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ldr.4481
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality assessment of cropland in China and its relationships with climate and topography

Abstract: Assessing soil quality (SQ) of cropland is fundamental for food security and sustainable land management. However, there is limited information regarding SQ assessment on a national scale, which is vital to answer important SQ-related questions in quantitative terms on that scale. Here, the SQ of cropland in China was assessed by constructing a minimum data set (MDS) from 23 soil physicochemical properties based on principal component analysis. The interaction roles and relative contributions of climate and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…The cropland quality that ranged from 0.2 to 0.4 had the largest area proportion (51.47%), followed by cropland quality between 0.4 and 0.6 (27.74%). These results showed good agreement with the previous study by Li et al (2022), which indicated the regions in the middle and lower reaches of the Yangtze River were dominated by low‐level soil quality. The lowest cropland quality (<0.2) is mainly concentrated in the western regions where the mountainous terrains adversely impacted farming activities.…”
Section: Resultssupporting
confidence: 92%
“…The cropland quality that ranged from 0.2 to 0.4 had the largest area proportion (51.47%), followed by cropland quality between 0.4 and 0.6 (27.74%). These results showed good agreement with the previous study by Li et al (2022), which indicated the regions in the middle and lower reaches of the Yangtze River were dominated by low‐level soil quality. The lowest cropland quality (<0.2) is mainly concentrated in the western regions where the mountainous terrains adversely impacted farming activities.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have shown that slopes and topographic relief increase the difficulty and cost of farming, as they require more labor, machinery, and inputs (Tarolli & Straffelini, 2020; He et al, 2020). They also affect cropland's soil quality and productivity, making it less attractive and viable for farming (Li et al, 2023). In addition, the terrain limits the construction and maintenance of transportation and irrigation facilities, which influences the accessibility and connectivity of cropland (Wang, Li, et al, 2020; Liu et al, 2019; Li et al, 2023), further restricting agricultural productivity (Liu, Song, et al, 2019; Wang, Li, et al, 2020), and creating barriers and isolation for farmers and markets (de Bruin et al, 2021; Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They also affect cropland's soil quality and productivity, making it less attractive and viable for farming (Li et al, 2023). In addition, the terrain limits the construction and maintenance of transportation and irrigation facilities, which influences the accessibility and connectivity of cropland (Wang, Li, et al, 2020; Liu et al, 2019; Li et al, 2023), further restricting agricultural productivity (Liu, Song, et al, 2019; Wang, Li, et al, 2020), and creating barriers and isolation for farmers and markets (de Bruin et al, 2021; Xu et al, 2020). Western China covers a large area with low population density and low level of economic development, farmers in western China tend to abandon their cropland and go out to find more profitable opportunities (He et al, 2020; Zang et al, 2020; Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%